Quantitative Evaluation of Infrared Absorbance Spectra – Lorentz Profile versus Lorentz Oscillator - Mayerhoefer, Thomas G.; Popp, Juergen (ChemPhysChem, 2019)
We present the theoretical basis for a profound upgrade of the method of absorbance band fitting (“band deconvolution”), which requires only minute changes in the code of corresponding spectrometer software. This upgrade is based on a (re-)connection of the damped harmonic oscillator model (“Lorentz oscillator”) and the Lorentz profile used for band fitting. Based on this reconnection, we provide a proper extension to multiple oscillators. As a result, band fitting allows directly obtaining all oscillator parameters with very good accuracy, at least for the not too strong oscillators present in organic and biological matter. Accordingly, this could be the initial spark to open the way to a long-awaited paradigm shift in infrared spectroscopy: Away from a mere oscillator position-based, towards an also intensity-based quantitative interpretation of spectra. As an extra, absorbance band fitting (“Poor Man's Dispersion Analysis”), allows to obtain the index of refraction function in one go.
CRIS-Team Scopus Importer:2023-04-20
Keywords: absorbance; band deconvolution; band fitting; dispersion analysis; IR spectroscopy